Examining the Role of Social Isolation on Stated Preferences - List, John A; Berrens, Robert P; Bohara, Alok K; Kerkvliet, Joe (American Economic Review, 2004)
Examining the Role of Social Isolation on Stated Preferences by John A. List, Robert P. Berrens, Alok K. Bohara and Joe Kerkvliet. Published in volume 94, issue 3, pages 741-752 of American Economic Review, June 2004